Church social teaching on migration. Issues and challenges - Tassello, Graziano (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2011)
The Church has always defended migrants’ rights, endorsing the right to free movement, family reunification, and the respect for immigrants’ cultural, linguistic and religious rights. The universal destination of the earth resources and the need for an international cooperation constitute the basis for the Church social teaching concerning migration. Faced with new challenges such as the illegal migration flows, the Church advocates the respect for the fundamental human rights and calls upon international norms capable of regulating the rights and duties of each person, with the aim of preventing unilateral decisions that cause harm especially to the low-income and poor people. She protects illegal immigrants through political advocacy and by running an extensive legal and charitable network in their favour. The Church social teaching on migration remains an unfinished task at the level of reflection. But through her teachings, the Church continues to sensitize public opinion and legislators by inputting ideals so that the fundamental rights of each person be respected and upheld everywhere and in every circumstance. Keywords: Church social teaching; Migration; Migrants’ rights; Illegal migration; Ethical A Igreja sempre defendeu os direitos dos migrantes, endossando o direito à livre circulação, reunificação familiar, e o respeito pelos direitos culturais, linguísticos e religiosos dos imigrantes. A destinação universal dos recursos da Terra e a necessidade de cooperação internacional constituem a base da doutrina social da Igreja com relação às migrações. Diante de novos desafios, como os fluxos de migrações ilegais, a Igreja defende o respeito pelos direitos humanos fundamentais e sugere normas capazes de regular os direitos e deveres de cada pessoa, com o objetivo de prevenir decisões unilaterais que causem danos especialmente para pessoas pobres e de baixa renda. Ela protege imigrantes ilegais por meio de demandas políticas e pela construção de uma extensiva rede legal e de caridade a favor dos mesmos. A doutrina social da Igreja em matéria de migração permanece uma tarefa inacabada no nível de reflexão. No entanto, através de seus ensinamentos, a Igreja continua sensibilizando a opinião pública e legisladores, introduzindo ideais a fim de que os direitos fundamentais de cada pessoa sejam respeitados e acolhidos em todos os lugares sob quaisquer circunstâncias. Palavras-chave: Doutrina social da Igreja; Migrações; Direitos dos migrantes; Migração ilegal; Questões éticas